„Wielka bitwa paryska”. O pierwszym francuskim wydaniu „Ferdydurke” - Rodak, Paweł (Wydawnictwo Naukowe UAM, 2013)
This article presents the story of the first French edition of Witold Gombrowicz’s Ferdydurke. The novel was published in October 1958 by the Julliard publishing house. The article is based on letters that Gombrowicz exchanged with Constantin Jelenski, a Polish essayist living in Paris and a great promoter of his work, as well as on Gombrowicz’s publishing-related correspondence with Maurice Nadeau, René Julliard and Pierre Javet. The article shows that Gombrowicz was a writer who paid great attention not only to the form of his works, but also to the way in which they reached the reader. Therefore, he attempted to influence, as much as possible, the manner in which his books would be published. He sought to establish a new way of presenting the writer to the reader that would fall outside the rules and conventions of world literature. The article shows why he succeeded in Poland and Argentina, but not in France, where he did not have followers.
“The great battle of Paris”: on the first French edition of Ferdydurke